Non-absorbing mirrors in mode-locked lasers - Tandoi, G.; McMaster, S.; Ironside, Charlie; Bryce, A. (2010)
We present results from GaAs/AlGaAs colliding-pulse mode-locked lasers with a repetition rate of 20GHz and wavelength of 830nm. Devices with and without non-absorbing mirrors are compared in terms of output power characteristics and mode-locking operation. ©2010 IEEE.